2012
DOI: 10.1371/journal.pone.0045664
|View full text |Cite
|
Sign up to set email alerts
|

Distance and Character-Based Evaluation of the V4 Region of the 18S rRNA Gene for the Identification of Diatoms (Bacillariophyceae)

Abstract: DNA barcoding is a molecular tool that exploits a unique DNA sequence of a standardized gene or non-coding region for the species identification of unknown individuals. The investigation into a suitable barcode for diatoms is ongoing and there are several promising candidates including mitochondrial, plastidial and nuclear markers. We analyzed 272 sequences from 76 diatoms species in the orders Thalassiosirales, Lithodesmiales and Cymatosirales, using distance and character based approaches, to assess the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…Thus, Luddington et al. (), using the highly variable V4 region of the nuclear 18S rRNA, found that a threshold of 0.02 successfully separated 96.9% of species tested and Moniz and Kaczmarska (), using a class‐specific threshold of 0.11 with the 5.8S‐ITS2 as marker and uncorrected genetic distances, were able to separate 95% of the species tested. The ITS‐based p ‐distances between P. plurisecta and its closest relatives were found to be slightly higher than 0.02 and higher than the values obtained when the strains of P. cuspidata / P. pseudodelicatissima were compared to each other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Luddington et al. (), using the highly variable V4 region of the nuclear 18S rRNA, found that a threshold of 0.02 successfully separated 96.9% of species tested and Moniz and Kaczmarska (), using a class‐specific threshold of 0.11 with the 5.8S‐ITS2 as marker and uncorrected genetic distances, were able to separate 95% of the species tested. The ITS‐based p ‐distances between P. plurisecta and its closest relatives were found to be slightly higher than 0.02 and higher than the values obtained when the strains of P. cuspidata / P. pseudodelicatissima were compared to each other.…”
Section: Discussionmentioning
confidence: 99%
“…This point is discussed by Luddington et al. () concerning diatoms and can be extended to other taxonomic groups with pseudocryptic or cryptic species (e.g., Laza‐Martínez et al. ).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…However, the level of taxonomic placement, for example, from phylum level to ecotype, is completely dependent on the depth and accuracy of the reference databases. For this reason, alignment and placement within phylogenetic trees remain the best method for accurately portraying diversity within groups of closely related organisms (10). While amplicon sequencing shares some of the inherent biases of other PCR-based methods (11,12), it is useful for highlighting differences and similarities among samples, provided similar protocols are followed.…”
mentioning
confidence: 99%
“…A number of examples have been published of species sharing sequences for a mitochondrial marker, although the problem is more widespread for 16S rDNA than for Cytochrome b or COI ([32], [16], [17]). 18S rDNA, while more useful for taxonomic assignment where no closely related sequences are available ([85], [86]) is more conserved than either 16S or COI in some taxonomic groups (table 3), and sometimes shows little or no divergence between some closely related species (table 3 and [82], [87]) distinguishable by mitochondrial markers (table 3 and [32]). When taking into account the error rates of the sequencing techniques, such low divergences can present serious pitfalls for differentiation of clades, as sequencing errors impose divergence thresholds to lower the risk of considering two clusters as distinct due solely to sequencing errors [88].…”
Section: Resultsmentioning
confidence: 99%